البيئة اللغوية لترقية مهارة الكلام باللغة العربية للطالبات الفصل السابع في معهد المؤمن للتربية الإسلامية نجروكي سوكاهارجو: البيئة اللغوية لترقية مهارة الكلام باللغة العربية للطالبات الفصل السابع في معهد المؤمن للتربية الإسلامية نجروكي سوكاهارجو - Synthia Rahmatika Syafitri synthia (Universitas Muhammadiyah Prof. Dr. Hamka, 2023)
Language is a communication tool or the most important symbol in human life, and Arabic is a second language that someone learns after acquiring the first language, then as a second language learner requires a supportive environment. This research aims at an in-depth analysis of the linguistic environment to improve the Arabic speaking skill of the seventh semester female students at the Al-Mukmin Islamic Boarding School Ngruki Sukoharjo. This research is a qualitative research using the case study method. As for the data collection techniques used by the researcher, it is through observation, interviews and documentation. And the results of the research say that the linguistic environment can be achieved from the vision, and it comes from the vocabulary and linguistic styles written on the walls of the institute, and for that, the formation of the linguistic environment in the Mumin Institute of Islamic Education Ngrokie Sukaharjo is classified into two parts: the formal language environment and the informal language environment. With regard to the official language environment, for example: if the teacher and professor present a course on the Arabic language in the classroom, such as Arabic grammar and Arabic structures. While in the informal language environment there are language support activities such as language rhyme, discussion, lecture, debate, language court. Keywords: linguistic environment, Arabic language, linguistic activities